2018
DOI: 10.1002/jib.496
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of antioxidants in distilled spirits by a silver nanoparticle assay

Abstract: Ingestion of antioxidants from the diet is associated with improved health. Total antioxidant capacity as gallic acid equivalents (GAE) of distilled spirits was determined using a modified and validated silver nanoparticle (SNaP) assay utilizing silver nanoparticles pre‐capped with starch and microwave technology. GAE concentrations determined by the SNaP assay for the distilled spirits were validated by high‐performance liquid chromatography (HPLC) measurements of key antioxidant components including gallic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…% RSD values of 1.4-3.19 % and 1.31-2.85 % for the peak areas of GA and EA, respectively, in the whiskeys (n = 3) indicate high reliability in the concentrations of the acids determined. Concentrations of 1-35 μM and 8-99 μM of GA and EA, respectively, are reported in unidentified Scotch whiskeys [27]. EA was also identified as the predominant phenolic constituent in both singlemalt Scotch (~33 μM) and blended Scotch (~17 μM) [28] whiskey.…”
Section: Detection Of Gallic and Ellagic Acids In Whiskey Samplesmentioning
confidence: 92%
“…% RSD values of 1.4-3.19 % and 1.31-2.85 % for the peak areas of GA and EA, respectively, in the whiskeys (n = 3) indicate high reliability in the concentrations of the acids determined. Concentrations of 1-35 μM and 8-99 μM of GA and EA, respectively, are reported in unidentified Scotch whiskeys [27]. EA was also identified as the predominant phenolic constituent in both singlemalt Scotch (~33 μM) and blended Scotch (~17 μM) [28] whiskey.…”
Section: Detection Of Gallic and Ellagic Acids In Whiskey Samplesmentioning
confidence: 92%
“…This work found that new make spirit had no antioxidant activity so maturation was entirely responsible for the production/extraction of the antioxidant/phenolic compounds ( 56 ) . In 2018, the total antioxidant capacity of distilled spirits was determined using synthesised silver nanoparticles, however this sample set only included four Scotch Whiskies ( 57 ) .…”
Section: Introductionmentioning
confidence: 99%